A study of risk factors for acute lower respiratory tract infections (ALRTI) in children aged 1 month to 5 years attending to a tertiary care hospital, Eluru, Andhra Pradesh, India - Dr. Manohar Bekkam; Dr. Arigela Vasundhara (Pediatric Review: International Journal of Pediatric Research, 2018)
Introduction: Acute respiratory infections are a leading cause of morbidity and mortality in under-five children in developing countries with nearly 156 million new episodes each year, of which India accounts for a bulk of 43 million. According to Child Health Epidemiology Reference Group (CHERG) latest estimates for 2010, pneumonia was responsible for 0.397 million of total estimated 1.682 million under-5 deaths in India.Objective: The present study was undertaken to study the various risk factors of Acute lower respiratory tract infections (ALRTI) in children aged 1 month to 5 years.Methods: In the present study100 ALRTI cases belong to the age group of 1 month to 5 years fulfilling WHO criteria for pneumonia who were attended to the department of Pediatrics, ASRAM Medical College from August 2017 to August 2018 were evaluated for risk factors after obtaining parental consent.Results: Parental illiteracy (p=0.000*), overcrowding (p=0.0000*), incomplete immunization (p=0.0000*), lack of exclusive breast feeding (p=0.0004*), low birth weight (p=0.000*), use ofbiomass fuels for lighting (p=0.0002*), mud/ cowdung flooring (p=0.0088*) were identified as potential risk factors for severe ALRTI.Conclusion: The present study has identified various socio-demographic, nutritional and environmental risk factors for ALRTI which can be tackled by effective health education of the community and effective training of peripheral health personnel.